Permafrost and periglacial research in Antarctica: new results and perspectives - Guglielmin, Mauro (2014)
In the last two years the research within the Antarctic Permafrost, Periglacial Environments and Soils (ANTPAS) Expert Group of the Scientific Committee on Antarctic Research (SCAR) andWorking Group of the International Permafrost Association (IPA) provided newresults on the dynamics of periglacial environments both inMaritime and Continental Antarctica. In continental Antarctica despite the absence of air warming, in the last 15 years an active layer thickening and acceleration of permafrost degradation erosional phenomena were reported, these beingmainly related to the increase of solar radiation. On the other hand, inMaritime Antarctica,with a dramatic airwarming, permafrost degradation has been observed, but the role of snowcover on the ground energy balance and consequently on permafrost and active layer has been underlined. Moreover, many contributions on the knowledge on the characteristics of the Antarctic soils were carried out in several areas along a wide latitudinal range.